2017
DOI: 10.1039/c7fo01348e
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of the bioaccessibility and bioavailability of Fe, Mn, Cu, and Zn in Chinese vegetables using thein vitrodigestion/Caco-2 cell model: the influence of gut microbiota

Abstract: The influence of the human gut microbiota on the bioaccessibility and bioavailability of trace elements in vegetables has barely been studied. An in vitro digestion model combining the physiologically based extraction test (PBET) and the Simulator of Human Intestinal Microbial Ecosystem (SHIME) was applied. Results showed that the gut microbiota increased the bioaccessibility of iron (Fe) in ten test vegetables by 1.3-1.8 times, but reduced the bioaccessibility of manganese (Mn), copper (Cu), and zinc (Zn) in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 43 publications
1
27
0
Order By: Relevance
“…It is noteworthy that Mn can create both problems of dietary deficiency, especially in developing countries, and toxicity, mainly due to environmental pollution and excessive levels in drinking water. 43,44 The possibility to modulate the mineral contents of microgreens, on the basis of either genetic diversity or agronomic parameters, is being explored, with the aim to provide appropriate supplementation or to reduce dietary exposure to single mineral nutrients. Significant results have been obtained for K, leading to the production of low-K microgreens which could be suitable for patients with impaired kidney function.…”
Section: Mineral Contentmentioning
confidence: 99%
“…It is noteworthy that Mn can create both problems of dietary deficiency, especially in developing countries, and toxicity, mainly due to environmental pollution and excessive levels in drinking water. 43,44 The possibility to modulate the mineral contents of microgreens, on the basis of either genetic diversity or agronomic parameters, is being explored, with the aim to provide appropriate supplementation or to reduce dietary exposure to single mineral nutrients. Significant results have been obtained for K, leading to the production of low-K microgreens which could be suitable for patients with impaired kidney function.…”
Section: Mineral Contentmentioning
confidence: 99%
“…For example, it was recently demonstrated that the bioavailability of iron from pea seeds varied at different stages of development due to phytate content (Moore et al, 2018). Similarly, Cai et al (2017) used simulated digestion and uptake by Caco-2 cells to estimate the bioavailability of iron in a number of Chinese vegetables in order to provide recommendations for consumers. The aim of this study was therefore to determine the bioaccessibility and bioavailability of iron in commonly consumed green vegetables in order to underpin dietary recommendations for alleviating IDA.…”
Section: Introductionmentioning
confidence: 99%
“…Mineral elements (MEs), such as copper (Cu), iron (Fe), manganese (Mn), and zinc (Zn), play important roles in maintaining health and are also essential nutrients for gut microbes (Cai et al, 2017;White & Brown, 2010). The gut is the major organ of mineral element digestion and absorption from the diet (Gopalsamy et al, 2015;Hara, Konishi, & Kasai, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The microbes housed in the gut play a conspicuous role in regulating the absorption of MEs, and are also influenced by dietary MEs (Reed et al, 2015). Intestinal microbes are conducive to the bioprecipitation, dissolution, bioaccessibility, and bioavailability of MEs (Cai et al, 2017;Carmichael, Carmichael, Santelli, Strom, & Bräuer, 2013;Bennett, 2004). Meanwhile, MEs also influence the metabolism and survival of microbes.…”
Section: Introductionmentioning
confidence: 99%